221k views
3 votes
Solve for the unknown:

2z - (z-1) = 5z - 15

User MLar
by
6.0k points

2 Answers

7 votes

Answer:

z=4

Explanation:

You would distribute the negative sign outside of the parentheses and get:

2z-z+1=5z-15

Then combine like terms and get:

z+1=5z-15

Subtract 5z from both sides:

-4z+1=-15

Subtract 1 from both sides:

-4z=-16

Then divide both sides by -4:

z=4



User PapaFreud
by
6.2k points
0 votes
z equals 4. See attached
Solve for the unknown: 2z - (z-1) = 5z - 15-example-1
User Tarun Maganti
by
5.6k points